Percepción de estudiantes sobre el clima escolar en instituciones de educación secundaria del noroeste de México (Investigaciones) - Juraz Rolón, Nicolás Eduardo (2024)
The objective was to analyze the school climate of secondary education institutions in northwest Mexico from the perception of students. The research is quantitative, non-experimental and descriptive in scope; 381 public secondary education students participated. A questionnaire was applied to evaluate the school climate with the purpose of describing the perception of the learning environment and the relationships of the actors in the educational process. To determine the psychometric properties of the scales, a maximum likelihood EFA and Oblimin rotation were performed. The “school climate” scale determined an underlying structure of seven factors. The “satisfaction and fulfillment of expectations” scale presents a unifactorial solution. The results describe statistically significant differences for the dimensions “relationship with the director”, “relationship with teachers” and “conflict resolution”. Students in the morning shift have higher averages compared to those in the afternoon shift. It is concluded that this study allows us to understand the way in which material and symbolic conditions, behavioral practices and relationships between agents in the school context are conceived. Based on this, intervention proposals can be proposed to improve the conditions of coexistence and school climate to develop a culture of peace.